2019
DOI: 10.1002/bimj.201800395
|View full text |Cite
|
Sign up to set email alerts
|

Power gains by using external information in clinical trials are typically not possible when requiring strict type I error control

Abstract: In the era of precision medicine, novel designs are developed to deal with flexible clinical trials that incorporate many treatment strategies for multiple diseases in one trial setting. This situation often leads to small sample sizes in disease‐treatment combinations and has fostered the discussion about the benefits of borrowing of external or historical information for decision‐making in these trials. Several methods have been proposed that dynamically discount the amount of information borrowed from histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 32 publications
3
58
1
Order By: Relevance
“…However there could be an inflation (or deflation) in the type one error rate and the marginal power of testing the corresponding hypothesis unless the positive (or negative) trend has a magnitude of less than 0.5% of the standard deviation (based on simulation results not presented here). This finding is similar to the finding of Kopp-Schneider et al [39] for the situation where external information is used in the inference of clinical trials: power gain is not possible when requiring a strict type one error rate control. When the recruitment to all arms do not finish simultaneously, the control data can be sepa-rated into before and after adding an arm and those after the initial treatment arms finish recruitment.…”
Section: Discussionsupporting
confidence: 89%
“…However there could be an inflation (or deflation) in the type one error rate and the marginal power of testing the corresponding hypothesis unless the positive (or negative) trend has a magnitude of less than 0.5% of the standard deviation (based on simulation results not presented here). This finding is similar to the finding of Kopp-Schneider et al [39] for the situation where external information is used in the inference of clinical trials: power gain is not possible when requiring a strict type one error rate control. When the recruitment to all arms do not finish simultaneously, the control data can be sepa-rated into before and after adding an arm and those after the initial treatment arms finish recruitment.…”
Section: Discussionsupporting
confidence: 89%
“…This can also be seen by considering the rejection regions presented for the clinical trial example ( Figure 5). Thus, in summary, our results are in line with the results of Kopp-Schneider et al 28 who argue that "borrowing of information cannot lead to an increased power while strictly controlling type I error." Our proposed procedure achieves this goal only in the two-arm borrowing and two-sided testing case by reducing the power to reveal a favorable treatment effect for the control group as compared to the treatment group, while still controlling the type I error at the prespecified significance level α.…”
Section: Discussionsupporting
confidence: 92%
“…Their approach corresponds to a Bayesian power prior approach with prespecified amount of borrowing. Their results seem to contradict the findings by Kopp-Schneider et al, 2 who showed that power gains from historical information are not possible when type I error rate should be controlled whenever a uniformly most powerful (UMP) test exists. Although not mentioned in the title nor in the abstract, the situation considered by Feißt and colleagues is the two-sided test setup for a two-arm comparison of a binary variable.…”
contrasting
confidence: 60%